2007
DOI: 10.1002/hed.20568
|View full text |Cite
|
Sign up to set email alerts
|

Management of frey syndrome

Abstract: Almost all patients who undergo parotidectomy will to some extent develop Frey syndrome (auriculotemporal syndrome or gustatory sweating) after surgery, because of aberrant regeneration of cut parasympathetic fibers between otic ganglion and subcutaneous vessels. However, only the minority of these patients needs treatment. The syndrome consists of gustatory sweating, flushing, and warming over the preauricular and temporal areas. Thick skin flap and partial superficial parotidectomy are the most important tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 43 publications
(41 reference statements)
4
91
0
3
Order By: Relevance
“…Hastalara özellikle çiğneme sonrası terleme olup olmadığı sorgulandığın-da ise yaklaşık %30-40 hastada bu semptomlara rastlanmaktadır. Ek olarak tanısal testlerle bakıldığında parotidektomi sonrası %95 oranında ilgili semptomlara rastlanmıştır (7,21) . Çalışmamızda, hastalar ortalama 21,7 ay takip edilmiş olup, Frey Sendromu literatürle karşı-laştırıldığında benzer oranlarda tespit edilmiştir.…”
Section: Discussionunclassified
“…Hastalara özellikle çiğneme sonrası terleme olup olmadığı sorgulandığın-da ise yaklaşık %30-40 hastada bu semptomlara rastlanmaktadır. Ek olarak tanısal testlerle bakıldığında parotidektomi sonrası %95 oranında ilgili semptomlara rastlanmıştır (7,21) . Çalışmamızda, hastalar ortalama 21,7 ay takip edilmiş olup, Frey Sendromu literatürle karşı-laştırıldığında benzer oranlarda tespit edilmiştir.…”
Section: Discussionunclassified
“…According to the literature, the incidence of Frey syndrome showed great variation, ranging from 2.6 to 97.6% [6], which could be explained by the different study designs, variable investigation periods with different diagnostic standards (e.g., objective testing [i.e., starch-iodine test] or the presence of clinical symptoms), and different surgical techniques. The presumed pathophysiology of Frey syndrome was that aberrant parasympathetic nerve outgrowth to the overlying sweat glands of the face caused the symptoms of sweating and flushing in association with eating [19,20]. Several prophylactic techniques based on the presumed pathophysiology have been proposed with the aim to place a barrier between the postganglionic parasympathetic nerve fibers and the sweat glands of the skin flap while at the same time preventing the connection in between [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that around 10% of patients undergoing parotidectomy will complain of gustatory sweating, however, on questioning, 30-40% will reply that they experience it, while it can be demonstrated objectively by starch-iodine test in 95% of patients. 8 The pathophysiology of this syndrome was described by Andre Thomas 9 in 1927 and later by Ford and Woodhall 10 in 1938. They postulated that Frey's syndrome is caused by aberrant regeneration of sectioned postganglionic parasympathetic fibers that are severed during parotidectomy.…”
Section: Surgical Technique Of Fascia Lata Interpositionmentioning
confidence: 99%